LEAF AREA INDEX DERIVED FROM HEMISPHERICAL PHOTOGRAPH AND ITS CORRELATION WITH ABOVE-GROUND FOREST BIOMASS - Basuki, Tyas Mutiara (Secretariat of Forestry Research and Development Agency, 2015)
Leaf area index (LAI) is one of the key physical factors in the energy exchange between terrestrial ecosystem and atmosphere. It determines the photosynthesis process to produce biomass and plays an important role in performing forest stand reflectance. Therefore building relationship between LAI and biomass from field measurements can be used to develop allometric equations for biomass estimation. This paper studies the relationship between diameter at breast height (DBH) and leaves biomass, DBH and crown biomass (sum up of leaves,Â twigs and branches) as well as between LAI and leaves biomass; LAI and crown biomass; LAI and Total Above-ground Biomass (TAGB) in East Kalimantan Province. Destructive sampling was conducted to develop allometric equations. The DBH measurements from 52 sample plots were used as training data for model development (35 plots) and for validation (17 plots). A hemispherical photograph was used to record LAI. The result shows that strong corelation (r) exists between natural logarithmic (ln) DBH and crown biomass ranging from 0.88 to 0.98. The correlation (r) between LAI and biomass of leaves; leaves + twigs + branches; TAGB were 0.742, 0.768 and 0.772, respectively.Â Improvement of (r) between LAI and biomass can be conducted by proper time of LAI measurement, when the sky is uniformly overcast.